Effect of Different Level of Cattle Manure on Growth Performance and Chemical Composition of Sweet Grass - KEOVILAYSAK , Viengsavanh; SILIVONG, Phonevilay (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This experiment was to compare the rate of cattle manure by increasing the level of cattle manure from 0, 10, 15 and 20 T/ha on growth performance of sweet grass, chemical composition of grass and soil. The located was conducted at Nanonghoung Village, Phieng District and Xayaboury Province and through from July to November 2022, there were 4 treatments and design in RCBD with 4 replications of each treatment. The treatments were: T1= No manure (Control treatment), T2= Manure in 10 T/ha, T3= Manure in 15 T/ha, and T4= Manure in 20 T/ha. The result showed that increasing the level of cattle manure from 0, 10, 15 and 20 T/ha were increased biomass of sweet grass and chemical composition of grass and soil and showed a curvilinear increase as the level of cattle manure from 0, 10, 15 and 20 T/ha, there fore can be increased fresh and dry biomass of sweet grass, therefore, it can be said that use of cattle manure may be an option to reduce the green house gass and to help environment, but on the other hand, it can be improve the soil fertility and improve the growth performance of sweet garss.